Health care waste disposal among private dentist in an Indian city: It’s time to act - Khandelwal, Vishal; Khandelwal, Sushma; Thakur, Jandel Singh (International Journal of Infection Control, 2013)
The provision of healthcare generates waste which can be detrimental to health and environment. Staff that provide dental healthcare ought to be aware of the proper handling and the system of management of dental waste used by different dental hospitals. A survey was conducted to determine the awareness of dental practitioners on hospital generation and handling of waste. A self-administered questionnaire was used. Lack of awareness, ignorance of policy and procedure on the handling of dental healthcare waste and failure to attend educational activities were major defects found among practitioners in the study. There is a need for a plan to improve the awareness of dental healthcare workers about hospital generated waste and its proper handling.